CYP1A gene expression as a basic factor for fipronil toxicity in Caspian kutum fish - Rashid Alijani Ardeshir; Hossein Zolgharnein; Abdolali Movahedinia; Negin Salamat; Ebrahim Zabihi (Toxicology Reports, 2018)
The aim of this study was to assess the effects of fipronil insecticide on the Caspian kutum fish at different levels of biological organizations and to find possible relationship between these biomarkers. Different doses of fipronil (65, 130 and 200 mg/kg) were intraperitoneally administered to the fish for 2 weeks. After 7 and 14 days of exposure, alterations in organ-somatic index, tissue and DNA structure, oxidative stress and CYP1A gene expression in gill, liver, brain and kidney were studied. Determination of these parameters in the liver showed that the degree of tissue change (DTC), comet tail, superoxide dismutase (SOD) and relative CYP1A mRNA expression increased mostly in a time dependent manner whereas in the kidney increased mostly in a dose dependent manner. These parameters in the gill increased more in time and dose dependent manner. Apart from the changes in CYP1A expression and oxidative stress, no alterations was observed in the brain. Multiple regression analysis showed that the CYP1A had the most correlation with the organ-somatic index (R2 = 0.76) and comet tail (R2 = 0.89) in the liver, and with DTC (R2 = 0.93) and oxidative stress (R2 = 0.87) in the kidney. Generally, this study showed that CYP1A gene expression can be considered as one basic factor for fipronil toxicity in this fish. However, other possible factors also should be considered for future research. Keywords: CYP1A gene, Oxidative stress, Comet assay, Fipronil